Control of a Pediatric Pulsatile Ventricular Assist Device: A Hybrid Cardiovascular Model Study. Issue 12 (16th June 2017) - Ferrari, Gianfranco; Di Molfetta, Arianna; Zieliński, Krzysztof; Fresiello, Libera; Górczyńska, Krystyna; Pałko, Krzysztof Jakub; Darowski, Marek; Amodeo, Antonio; Kozarski, Maciej
Abstract: The aim of this work is to study pediatric pneumatic ventricle (PVAD) performance, versus VAD rate (VADR) and native heart rate (HR) ratio Rr (VADR/HR). The study uses a hybrid model of the cardiovascular system (HCS). HCS consists of a computational part (a lumped parameter model including left and right ventricles, systemic and pulmonary arterial and venous circulation) interfaced to a physical part. This permits the connection of a VAD (15 mL PVAD). Echocardiographic and hemodynamic data of a pediatric patient (average weight 14.3 kg, HR 100 bpm, systemic pressure 75/44 mm Hg, CO 1.5 L/min) assisted apically with asynchronous PVAD were used to set up a basal condition in the model. After model tuning, the assistance was started, setting VAD parameters (ejection and filling pressures, systole duration) to completely fill and empty the PVAD. The study was conducted with constant HR and variable VADR (50‐120, step 10, bpm). Experiments were repeated for two additional patients' HRs, 90 and 110 bpm and for two values of systemic arterial resistance ( R as ) and E max . Experimental data were collected and stored on disk. Analyzed data include average left and right ventricular volumes (LVV, RVV), left ventricular flow (LVF), VAD flow (VADF), and total cardiac output (COt). Data were analyzed versus Rr. LVV and RVV are sensitive to Rr and a left ventricular unloading corresponds in general to a right ventricular loading. In the case of asynchronous assistance, frequency beats are always present and the beat rate is equal to the difference between HR and VADR. In the case of pulsatile asynchronous LVAD assistance, VADR should be chosen to minimize frequency beat effects and right ventricular loading and to maximize left ventricular unloading.